2018
DOI: 10.3389/fphar.2018.01198
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Effects of Extended Sessions of Transcranial Direct Current Stimulation (tDCS) Over Dorsolateral Prefrontal Cortex on Craving and Relapses in Crack-Cocaine Users

Abstract: Background: Non-invasive brain stimulation such as transcranial direct current stimulation (tDCS) has been investigated as additional therapeutic tool for drug use disorder. In a previous study, we showed that five sessions of tDCS applied bilaterally over the dorsolateral prefrontal cortex (dlPFC) reduced craving to the use of crack-cocaine in inpatients from a specialized clinic. In the present study, we examine if an extended number of sessions of the same intervention would reduce craving even further and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 42 publications
0
24
0
Order By: Relevance
“…In our study, applying the right anodal active tDCS, which has more evidence in reducing craving in different studies, could not significantly reduce the relapse rate in patients with opioid dependence disorder enrolled MMT program (Klauss et al, 2018;Taremian et al, 2019). However, after seventh session of tDCS, the intervention group had lower relapse rate compared to the sham group.…”
Section: Effects On Relapsementioning
confidence: 51%
“…In our study, applying the right anodal active tDCS, which has more evidence in reducing craving in different studies, could not significantly reduce the relapse rate in patients with opioid dependence disorder enrolled MMT program (Klauss et al, 2018;Taremian et al, 2019). However, after seventh session of tDCS, the intervention group had lower relapse rate compared to the sham group.…”
Section: Effects On Relapsementioning
confidence: 51%
“…cocaine, tobacco), recent studies have examined the effects of repeated tDCS sessions over the DLPFC [37e39]. All of these studies, except for Klauss et al [37], observed increased effects of extended stimulation on reduced craving in patients, although none of them have examined executive dysfunctions.…”
Section: Introductionmentioning
confidence: 99%
“…However, the number of studies investigating the effect of neuromodulation on the cognitive processes involved in addiction remains limited [11], precluding any firm conclusion about cognition-improving effects and clinical efficacy [11,41]. The fact that most other studies on drug addictions have targeted craving as the main outcome parameter [37,38] or applied short durations of DLPFC stimulation, which may not be clinically effective [42,43], makes it furthermore difficult to come to definite assumptions. In order to evaluate the potential of tDCS in addiction, including its effects on cognitive deficits, trials with longer courses of stimulation, as suggested by recent findings [42], inclusion of objective neurophysiological and cognitive measures, and monitoring of long-term outcomes would be helpful [11].…”
Section: Introductionmentioning
confidence: 99%
“…Acute multiple sessions of tDCS stimulation protocols, typically related to facilitative effects on cortical excitability (Nitsche and Paulus, 2000;Paulus, 2003), have been associated with a reduction of spontaneous (Batista et al, 2015;Klauss et al, 2018b), and cue-induced craving (Boggio et al, 2009;Fregni et al, 2008;Gorelick et al, 2014) when applied over the prefrontal cortex. However, there was no effect on spontaneous craving when stimulation sessions were extended (Klauss et al, 2018a). Similarly, rTMS protocols at high frequency (5-25 Hz) have typically been used to excite cortical neurons and elicit LTP-like effects.…”
Section: Tes/tms Dosage In the Treatment Of Sudsmentioning
confidence: 99%